Diagnosing active and latent tuberculosis among Iranian HIV‐infected patients. (27th April 2016) - Baghaei, Parvaneh; Esmaeili, Shahrbanou; Farshidpour, Maham; Javanmard, Pedram; Marjani, Majid; Moniri, Afshin; Nemati, Kambiz; Tabarsi, Payam
Abstract: Objective: To screen for Tuberculosis (TB) in human immunodeficiency virus (HIV) people in an effort to improve early TB diagnosis and reduce TB transmission. Methods: A prospective study was conducted on adult HIV people from 2008 to 2011. Three samples of sputum, cell blood count, tuberculin skin test (TST) and chest X‐ray were obtained from all patients. The characteristics of HIV patients with TB and HIV patients without TB were compared to each other. Results: Of the 154 HIV patients included, 58 (38%) had tuberculosis with a mean CD4 cell count of 68 cells/mm 3 . Active TB was found in 56 (47%) patients with a history of intravenous drug use. Cough (OR = 3.1, 95% CI 1.2–7.79), positive TST (OR = 8.15, 95% CI 3.28–20.25) and an abnormal chest X‐ray (OR = 5.1, 95% CI 1.84–14.2) were the predicting factors for detecting active TB among HIV patients. The sensitivity and specificity of a combination of any symptoms with chest X‐ray, smear, TST or all of these were 96.5% and 86.5%, respectively. CD4 cell count <100 (OR = 2.67; 95% CI 1.23–5.78) and smoking (OR = 13.4; 95% CI 3.04–59.4) remained independently associated with TB in a multivariate analysis. Conclusion: There was a high prevalence of TB within the HIV population. Screening for TB among these patients can be carried out at every clinic or health facility using a combination of symptoms, TST, chest X‐ray and smear sample.